2018
DOI: 10.3390/ijerph15091967
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Its Influencing Factors among the Elderly in a County, Guangxi Province, China

Abstract: Objectives: This study aims to understand the disability status of the elderly residents of a County (Guangxi Province, China) and explore its influencing factors. Methods: Respondents consisted of 2300 elderly people aged 60 and above from three townships in the county we studied. The Activities of Daily Living (ADL) Scale was used to assess the disability of the elderly sample. Chi-square test was applied to compare the disability rate among the elderly with different demographic characteristics. The graph s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 48 publications
(56 reference statements)
4
23
1
Order By: Relevance
“…In this study, we found the prevalence rate of functional disability to be 43%, which is consistent with the reported prevalence rate of 43.4% among elderly people aged 60 years and above in Guangxi province, China [9], but higher than the prevalence rate (18%) in Irish elderly people aged 65 and above [35]. This inconsistency may be due to different cultural and historical contexts between two countries as well as different samples and investigation scales.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study, we found the prevalence rate of functional disability to be 43%, which is consistent with the reported prevalence rate of 43.4% among elderly people aged 60 years and above in Guangxi province, China [9], but higher than the prevalence rate (18%) in Irish elderly people aged 65 and above [35]. This inconsistency may be due to different cultural and historical contexts between two countries as well as different samples and investigation scales.…”
Section: Discussionsupporting
confidence: 88%
“…The Cronbach's α of the questionnaire was 0.925. The results of this scale in China have been proven reliable and robust [9].…”
Section: Measurement Of Functional Disabilitymentioning
confidence: 84%
See 2 more Smart Citations
“…If no drugs were taken within 3 months, it would be determined as no and valued as "1", otherwise the value would be "0". We applied activities of daily living (ADL) to evaluate whether the participants were disabled [25] . If participants had the ability to independently conduct six activities in their daily life, they were diagnosed as non-disabled, with a value of "1".…”
Section: Variable Selectionmentioning
confidence: 99%